Obesity: A Review of Pathogenesis and Management Strategies - Brinderjit Kaila; Maitreyi Raman (Canadian Journal of Gastroenterology)
The prevalence of obesity in the developed world is increasing. Approximately 23% of adult Canadians (5.5 million people) are obese. Obesity is associated with an increased risk of developing several comorbid diseases, ranging from cardiovascular diseases to cholelithiasis and nonalcoholic fatty liver disease. The etiology of obesity is multifactorial, involving a complex interaction among genetics, hormones and the environment. The available evidence and recommendations for nonpharmacological management of obesity, including dietary therapy, physical activity and behavioural therapy, in addition to pharmacotherapy are discussed. A brief discussion on endoscopic and surgical procedures is undertaken. Several antiobesity treatment options are available and may be indicated in appropriate situations. Selecting obesity therapy may be guided by body mass index measurements, comorbid illnesses and patient preference.